Peran Teknologi Informasi dalam Layanan Online Perpustakaan Masa Pandemi Covid-19 - Fitka Ayu Puspita; Bachrul Ilmi (Jurnal Pustaka Ilmiah, 2022)
The Covid-19 pandemic has attacked various levels of society from all parts of the world, including Indonesia. Many of the people affected by Covid-19 have begun to adapt to the new situation in various ways. Libraries as sources of information are required to adapt to the needs of their users. The author uses literature studies or literature reviews in compiling this paper. The role of technology in the pandemic period provides convenience in using the library. Librarians adapt services online: consulting services, digital source tracing services, plagiarism checking services, and building digital libraries. The role of technology in libraries in providing services during the Covid-19 pandemic requires librarian skills in understanding the tools used. Media Zoom, GMeet, WhatsApp, Youtube, Instagram, library websites are indispensable in disseminating information. The purpose of this paper is to explain how the role of information technology, especially from online services in libraries, in order to meet the information needs of users. The results of this paper can be concluded that libraries have an important role in disseminating information through the role of technology during the Covid-19 pandemic.